Effect of aspartic acid on the hydration process and setting performance of hemihydrate gypsum under alkaline conditions - Yi Hui; Jiacan Lin; Yi Ding; Qifang Ren; Ranran Chen (Journal of Materials Research and Technology)
This study employs Ca(OH)2 (CH) as an alkaline regulator to adjust the pH of β-hemihydrate gypsum (β-HH), and l-aspartic acid (LA) as a retarder. The effects of LA on the hydration performance of β-HH under different alkaline conditions were investigated. Results indicate that at pH 6.82, with 0.5 % LA added, the initial setting time of β-HH is 57 min and the final setting time is 110 min. At pH 11.03, with 0.5 % LA added, the initial setting time extends to 166 min and the final setting time to 450 min. Characterization techniques, including scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), TAM-Air isothermal calorimetry, and thermogravimetric (TG) analysis, confirmed that in an alkaline environment, LA significantly inhibits the dissolution of β-HH, thereby suppressing the crystallization of dihydrate gypsum (DH). Additionally, molecular dynamics (MD) simulations revealed that LA selectively adsorbs onto the (1 2 0) surface of DH crystals. The adsorption mechanism involves electrostatic interactions between the charged functional groups of LA and calcium ions on the gypsum surface, as well as hydrogen bonding between the additional carboxyl and amino groups of LA and water molecules.